RNAi for plant improvement and protection (CABI, 2023)
This book contains a series of chapters reviewing the current scientific knowledge on RNAi, methods for developing RNAi systems in transgenic plants and a range of applications for crop improvement, crop production and crop protection. Some chapters examine both endogenous systems in transgenic plants and exogenous systems where interfering RNAs are applied to target plants, pests and pathogens. The biosafety of these different systems is examined and methods for risk assessment for food, feed and environmental safety are discussed. Finally, aspects of the regulation of technologies exploiting RNAi and the socioeconomic impacts of RNAi technologies are discussed.